Factors influencing Sudanese microfinance intention to adopt mobile banking - Anwar Ammar; Elsadig Musa Ahmed (Cogent Business & Management, 2016)
Access to financial service has become a key phenomenon for economic development and poverty alleviation .Microfinance is one way of fighting poverty in Sudan, where most citizens are in need of it. However, despite the initial results showing a positive impact of microfinance on the livelihood of low-income people in Sudan, around 8 million of the Sudanese poor people are excluded from microfinance services. One potential remedy for the limited outreach of microfinance in Sudan may lie within enhancing the capacity of microfinance services providers (MFPs) in the utilization of modern technology. Recent innovation in providing financial services in a convenient and efficient way is the use of mobile banking (m-banking) technology in microfinance. M-banking promises to increase the efficiency and outreach of microfinance services in developing countries. This paper tries to examine the factors that influence the adoption of m-banking by microfinance sector in Sudan. In this respect, hypotheses were developed guided by Unified Theory of Acceptance and Use of Technology (UTAUT) and Technology-organization-Environment (TOE) models. Primary data were collected from MFPs and microfinance customers in Sudan using questionnaires and interviews. The study contributes to knowledge in terms of methods used by extending aforementioned theories through adding new variables to both models by putting both models in one study to fill the gaps in past studies; via examination of the demand (customers) and supply (institutions) through modifying them to include new variables related to m-banking in microfinance.
Keywords: 650